Finfish Aquaculture Diversification 2010
DOI: 10.1079/9781845934941.0417
|View full text |Cite
|
Sign up to set email alerts
|

The wolffishes (family: Anarhichadidae).

Abstract: In this chapter, the biology, description, culture, broodstock management, hatchery husbandry, on-growing to market stage of the wolffishes (Family: Anarhichadidae) are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The Atlantic Wolffish Anarhichas lupus is a boreal, marine species distributed on both sides of the North Atlantic Ocean. In the eastern Atlantic Ocean, Atlantic Wolffish is an important fishery species and has potential for aquaculture (e.g., von Beese and Kändler 1969;Jónsson 1982;Moksness and Pavlov 1996;Le Franc ¸ois et al 2010. Recent assessments in the North Sea suggest declines in abundance and contractions in geographic distribution consistent with effects of fishing pressure and climate change (Bluemel et al 2022), similar to that reported for other fishery species in the deep sea (e.g., Lloret et al 2021).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The Atlantic Wolffish Anarhichas lupus is a boreal, marine species distributed on both sides of the North Atlantic Ocean. In the eastern Atlantic Ocean, Atlantic Wolffish is an important fishery species and has potential for aquaculture (e.g., von Beese and Kändler 1969;Jónsson 1982;Moksness and Pavlov 1996;Le Franc ¸ois et al 2010. Recent assessments in the North Sea suggest declines in abundance and contractions in geographic distribution consistent with effects of fishing pressure and climate change (Bluemel et al 2022), similar to that reported for other fishery species in the deep sea (e.g., Lloret et al 2021).…”
mentioning
confidence: 58%
“…In the eastern Atlantic Ocean, Atlantic Wolffish is an important fishery species and has potential for aquaculture (e.g., von Beese and Kändler 1969; Jónsson 1982; Moksness and Pavlov 1996; Le François et al. 2010, 2021). Recent assessments in the North Sea suggest declines in abundance and contractions in geographic distribution consistent with effects of fishing pressure and climate change (Bluemel et al.…”
Section: Figurementioning
confidence: 99%
“…Foss and Imsland (2002) observed growth compensation and improved food conversion efficiency (FCE) after exposure to low oxygen concentration followed by a return to normoxic conditions. in somewhat different habitats, are depth-stratified and have distinct feeding strategies (Lait & Carr, 2018;Le François et al, 2010). Both species display different growth rates and optimal growth temperature (A. minor displays a higher growth rate at lower temperatures) (Le François, Fairchild, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, aquaculture of wolffish (spotted wolffish, Atlantic wolffish and/or their hybrids) is set to take place in Canada (Le François, Fairchild, et al., 2021) and the foreseen rearing technology, land‐based recirculated aquaculture systems (RAS) using low‐level raceways, can potentially generate chronic and acute DO variations due to limited water renewal, volumes involved and elevated fish densities (Foss et al., 2004; Le François et al., 2013; Tremblay‐Bourgeois et al., 2010: 200–300 kg/m 3 ); underlining the importance of evaluating potential long‐term effect of prolonged hypoxia exposure such as growth reduction, reduced appetite, alteration of metabolic pathways, re‐allocation of energy resources, poor feed conversion efficiency and prolonged digestion (Shen et al., 2023; Wang et al., 2009). Hybrids were included in the study because (1) they are of potential interest for aquaculture (Le François et al., 2010); (2) their growth rate was never examined at this size range and (3) hybridization can cause disruption of co‐adaptations of the mitochondrial and nuclear genomes, which in turn can alter aerobic metabolism and increase oxidative stress (functional incompatibilities) and potentially result in (3) decreased fitness (hybrid breakdown phenomenon) (Blier et al., 2006; Du et al., 2017; Gaudreau et al., 2013; Mathers et al., 2014) or (4) improved fitness‐related traits ‘hybrid vigour’ resulting in greater hypoxia tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation